2016
DOI: 10.1111/1475-6773.12588
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Nursing Home Compare and the Discharge from Hospitals to Nursing Homes

Abstract: Objective To test whether use of a personalized report card, Nursing Home Compare Plus (NHCPlus), embedded in a reengineered discharge process, can lead to better outcomes than the usual discharge process from hospitals to nursing homes. Data Sources/Setting Primary data collected in the Departments of Medicine and Surgery at a University Medical Center between March 2014 and August 2015. Study Design A randomized controlled trial in which patients in the intervention group were given NHCPlus. Participants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 15 publications
1
57
0
2
Order By: Relevance
“…First, Medicare prohibits hospitals from limiting patients' choice of PAC providers, and while hospitals are allowed to provide information about quality to patients and give them information about preferred partners, many hospital leaders and front‐line discharge personnel are not aware that such “steering” is in fact legal . Of course, even if provided with such information, patients may instead choose PAC providers that are close to their home, recommended by family or friends, or score well on Nursing Home Compare . It is also possible that such networks are time intensive for hospitals to create, and their use may not be reflected in current data; work with longer‐term follow‐up will be important in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…First, Medicare prohibits hospitals from limiting patients' choice of PAC providers, and while hospitals are allowed to provide information about quality to patients and give them information about preferred partners, many hospital leaders and front‐line discharge personnel are not aware that such “steering” is in fact legal . Of course, even if provided with such information, patients may instead choose PAC providers that are close to their home, recommended by family or friends, or score well on Nursing Home Compare . It is also possible that such networks are time intensive for hospitals to create, and their use may not be reflected in current data; work with longer‐term follow‐up will be important in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This research was not designed to answer the question if one set of weights is preferred to another. It was motivated by prior studies, discussed in the introduction, suggesting that consumers may find the expert opinion lacking . And perhaps the best approach, in an era of transparency enabled by current information and web technology, is to offer consumers a choice, of both an “expert‐based” 5‐Star and a “consumer like you” 5‐Star ranking.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent California study that elicited preferences from patients and their family members at the time of hospital discharge to NHs suggests that individuals often value quality dimensions differently than the expert-based 5-Star ratings. [8][9][10] However, fully personalizing NH ratings imposes its own cognitive burdens on those selecting NHs. Are there feasible alternative ways to incorporate consumer preferences into decisions about summary scoring?…”
Section: Weimer Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the papers focused on the relationship between process improvement and outcomes of care. In a randomized controlled trial, Mukamel et al (2016) found that personalizing nursing home report cards for patients and their caregivers improved satisfaction with the choice process, increased the likelihood of choosing a highly ranked nursing home, and led to shorter hospital stays. Johnston and Hockenberry (2016) found that receiving care from a disease-relevant specialist was associated with lower rates of following-year functional impairment, long-term care institutionalization, and ambulatory care-sensitive hospitalization, among Medicare beneficiaries with diabetes or heart failure.…”
mentioning
confidence: 99%